Cognitive load factors in instructional design for advanced learners - Kalyuga, Slava (Nova Science Publishers, 2009)
"The empirical evidence described in this book indicates that instructional designs and procedures that are cognitively optimal for less knowledgeable learners may not be optimal for more advanced learners. Instructional designers or instructors need to evaluate accurately the learner levels of expertise to design or select optimal instructional procedures and formats. Frequently, learners need to be assessed in real time during an instructional session in order to adjust the design of further instruction appropriately. Tradition testing procedures may not be suitable for this purpose. The following chapters describe a cognitive load approach to the development of rapid schema-based tests of learner expertise. The proposed methods of cognitive diagnosis will be based on contemporary knowledge of human cognitive architecture and will be further used as means of optimizing cognitive load in learner-tailored computer-based learning environments.'--P. [vii].